Reconstructive Surgery of Ulnar Claw Hand in Leprosy Patients by Lasso Procedure: Life Sciences-Orthopaedics - Mahapatra, Dr. Pratik; Reddy, Dr. Vijay Narasimman (International Journal of Life Science and Pharma Research, 2022)
Leprosy, Hansen's disease caused by mycobacterium leprae, is widely known. Though there has been a substantial achievement in recent years given eliminating the disease, the deformity caused by the disease needs to be managed by reconstructive surgery. The ulnar nerve being superficial, is the most common nerve affected. When affected, the muscles innervated by the nerve begin to weaken, leading to a disparity between the strong extrinsic muscles and the weakened intrinsic muscles and is characterized clinically by metacarpophalangeal joint hyperextension and flexion of the proximal and distal interphalangeal joint. Doing reconstructive surgery on these patients will help them carry out day-to-day activities and reduce social awkwardness. Corrective surgeries like modified Stiles-Bunnell transfer, extensor carpi radialis graft, Zancolli lasso procedure, and palmaris longus tail graft are known to us. Out of all, the Zancolli lasso procedure was chosen for operating on all our cases because all other surgeries need high precision with proper training and proper post-operative physiotherapy. The study aims to evaluate the functional outcome of patients with leprotic ulnar claw hand operated with the Zancolli lasso procedure. Objectives assessed were deformity correction, grip strength, and range of motion. During the last two years, ten patients with ulnar claw hands came to Sree Balaji Medical College and Hospital, Chennai. They were operated on with the Zancolli Lasso procedure with adequate results. The zancolli procedure is easy to do and can be done in small centers, which restores finger flexion and doesn’t harm other superficialis tendons, thus preventing swan neck deformity of the fingers.